Human factors training. Issue 12 (December 2021) - Howie, Emma; Yule, Steven
Abstract: The aim of this article is to introduce the concept of human factors training, illustrate the importance of human factors to safe surgical care, and clarify the relationship between human factors science and non-technical skills.